Analysis of characteristics of vulvo-vaginal infections in 14- to 18-year-old girls in late puberty. Issue 8 (August 2020) - Xu, Ling; Hu, Zhengqiang; Yu, Fan; Tang, Yuanting
Objective: This study aimed to determine the characteristics of vulvo-vaginal infections in 14- to 18-year-old girls in late puberty. Methods: From July 2016 to June 2019, 487 14- to 18-year-old girls with vulvo-vaginal infection in late puberty in West China Second University Hospital were retrospectively studied. The incidence of bacterial vaginosis (BV), the intermediate type of BV, vulvo-vaginal candidiasis (VVC), Trichomonas vaginalis (TV), and differences among the incidence of these infections for patients with different ages were analyzed. Results: The incidence of BV, the intermediate type of BV, TV, VVC, and unknown pathogenic vaginitis was 25.67%, 19.30%, 2.46%, 29.37%, and 23.20%, respectively. The incidence of BV and VVC was significantly higher than that of TV. The incidence of BV in the 17-year-old group was significantly higher than that in other age groups. The incidence of VVC and non- albicans Candida infection in the 17- and 18-year-old groups was significantly higher than that in the 14-year-old group. Conclusion: Girls in late puberty are more susceptible to suffer from BV and VVC than TV infections. Therefore, more attention should be paid to the effects of menstrual hygiene, female estrogen levels, the vaginal internal environment, and hygiene in vulvo-vaginal infection at this stage.